Management of renal cell carcinoma presenting as inflammatory renal mass - Ehab Eltahawy; Mohamed Kamel; Mahmoud Ezzet (Urology Annals, 2015)
Introduction: Renal cell carcinoma (RCC) can have a wide spectrum of clinical presentations. In the immunocompromised patient fever and an inflammatory renal mass can harbor RCC. Materials and Methods: We reviewed the charts of patients who were managed at our department during 1998-2008 as renal abscess or perinephric collection. Renal ultrasound and subsequently abdominal CT was done. Medical treatment in the form of antibiotics, control of diabetes and drainage was done. Percutaneous or open biopsy, pus cultures, and histopathology were used to guide therapy. With a positive biopsy radical surgery was considered, while with a negative result a follow up CT was planned. Results: We identified 11 patients who had high fever, a renal abscess (in 4), or a suspicious mass with perinephric collection (in 7), and were eventually diagnosed to have RCC. Mean patient age was 66 years (53-82). 8 patients had uncontrolled diabetes. Five patients had a percutaneous drainage biopsy; of those two had a positive histopathology, the other three patients had a persistent enhancing mass on follow-up CT scan. Of this group three patients underwent radical nephrectomy. Another five patients had open drainage and biopsy, four patients had very poor performance status. One patient had radical surgery without the need for biopsy. Conclusion: In the elderly and immunocompromised patient renal cancer may present as renal abscess or perinephric collection. Histopathology and bacteriology are the mainstay of diagnosis. If biopsy was negative, follow up should include a CT scan to exclude any residual enhancing masses.